DESEMPENHO DE CULTIVARES DE CYNODON, SOB CONDIÇÃO DE IRRIGAÇÃO, NO SEGUNDO ANO DE CULTIVO - Bronzatti, Rômulo; Uhde, Leonir T.; Rupollo, Carlos Z.; Bergoli, Luís M. G.; Jezewski, Tiago J.; Sartori, Cesar O. (Salão do Conhecimento, 2013)
Resumo